(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Brinjal is the second most important vegetable crop after potato in Bangladesh in respect of total areas and third in production. It also plays a vital role in the national economy as a cash crop. An experiment was conducted with two cultivars of brinjal namely Jhumky and Islampuri to observe the callus induction ability of different explants-shoot tip, hypocotyl and midrib in MS basal media supplemented with different concentrations and combinations of growth regulators. The rate of callus induction from shoot tip, hypocotyl and midrib were 82.78%, 74.88% and 78.71%, respectively. Highest rate of callus induction was found in shoot tip. Variety Islampuri showed higher rate of callus induction (80.62%). Among the treatments 2mg/l NAA showed the best performance in callus proliferation. Cytokinin (0.5 mg/l BAP) showed highest percentage of shoot regeneration (57.13%). For root induction, MS basal medium was proved to be better treatment for average number (12-15) of roots. The survival rate of transferred regenerated plantlets after hardening was higher in Jhumky (80%). Regenerated plantlets from callus of both the varieties exhibited 4-9 times higher proline, 2-3 times lower vitamin C and 2-3 times higher iron (Fe) content compared to their seed derived seedlings. This experiment showed that it is possible to develop shoot and fruit borer tolerance brinjal genotypes through somatic embryogenesis that was selected based on biochemical markers within the very short period of time. These findings will be helpful for further selection of the selected variants in field condition in the next phase of the study. Keywords: Somaclonal variants; Biochemical markers; Brinjal DOI: 10.3329/jbau.v7i2.4731 J. Bangladesh Agril. Univ. 7(2): 253-258, 2009